2014
DOI: 10.1002/jctb.4418
|View full text |Cite
|
Sign up to set email alerts
|

Hydrophobic ionic liquids as novel extractants for gold(I) recovery from alkaline cyanide solutions

Abstract: BACKGROUND: Although ionic liquids (ILs) as green solvents have become a focus of research in the field of metal ions separation, little attention has been paid to gold(I) recovery from alkaline cyanide solutions using ILs as extractants. Therefore, this work explores gold(I) extraction using hydrophobic imidazolium-based ionic liquids.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
21
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 43 publications
1
21
0
Order By: Relevance
“…[1,9] They have consequently been considered for a variety of applications such as separation technology, [10,11] catalysis, [12][13][14] biomass treatment [15,16] and energy storage. [1,9,17,18] For industrial applications of IL as alternative green solvents, the determination of both decomposition and melting temperatures is of paramount importance.…”
mentioning
confidence: 99%
“…[1,9] They have consequently been considered for a variety of applications such as separation technology, [10,11] catalysis, [12][13][14] biomass treatment [15,16] and energy storage. [1,9,17,18] For industrial applications of IL as alternative green solvents, the determination of both decomposition and melting temperatures is of paramount importance.…”
mentioning
confidence: 99%
“…17 Ionic liquids have been used to study the electrochemical dissolution/deposition of gold as a method for avoiding the use of cyanide. [21][22][23] In addition Qin et al have studied the immersion deposition of gold from tetrachloridoauric acid in the ionic liquid butylmethylimidazolium hexafluorophosphate onto zinc substrate. 24 Wang et al showed that uniform and bright ENIG coatings could be obtained from a solution of 500 g L -1 choline chloride in water adjusted to pH 2 with HCl and 1 g L -1 tetrachloridoauric acid.…”
mentioning
confidence: 99%
“…aqueous two phase systems (ATPs), leached using aqueous alkaline cyanide (AAC), cloud point extraction (CPE), liquid-liquid microextraction, microemulsion extraction, and ion exchange extraction [65][66][67][68][69] . IL extraction is a potential alternative method to separate gold from mixture of metal ions.…”
Section: Performance and Modified Of Ionic Liquids Extraction In Goldmentioning
confidence: 99%
“…IL extraction is a potential alternative method to separate gold from mixture of metal ions. As an example, (1-butyl-3-methylimidazolium hexafluorophosphate ([C4MIM][PF6])) is known has potential to increase solubility of metal include Au nanoparticles 65,70 . ILATPs have made interest pay attention for some recent researchers to separate gold in industrial scale since currently to recover gold from secondary source acid leaching or organic solvent extraction is still used.…”
Section: Performance and Modified Of Ionic Liquids Extraction In Goldmentioning
confidence: 99%
See 1 more Smart Citation